KONSEP FRUGAL LIVING DALAM MENCIPTAKAN KELUARGA SAKINAH PERSPEKTIF MAQASHID AL-SYARI’AH (Studi Kasus Alumni PPP. Walisongo Desa Cukir Kecamatan Diwek Kabupaten Jombang) - Umi Yuniatin Maulidah; Abdullah Afif (JOURNAL SAINS STUDENT RESEARCH, 2024)
The Frugal Living concept in creating a sakinah family according to student alumni PPP Wali Songo. Have full awareness and careful consideration regarding financial management and strategies for the future. The concept of Frugal Living itself is choosing food cooked at home because the price is relatively more economical, buying things you need instead of what you want by wasting money unnecessarily. In the Frugal Living concept, this does not mean being stingy but knowing when to spend money according to your needs. The Frugal Living concept makes individuals calmer and not confused about the excess wealth owned by other people. Thus, this attitude is very good and in accordance with Islamic teachings which uphold goodness.The aim of this research was to determine the concept of Frugal Living for alumni PPP Wali Songo to create a sakinah family and what efforts are made to create a sakinah family in the household.This research is empirical qualitative research. In obtaining the data, the author's research used three data collection techniques, namely interviews, observation and documentation. The author uses data interpretation in the form of facts in the field.The conclusion from the research in general is that in the application of Islamic law. Sakinah is included in the maqosid sharia theory, which is a theory for the realization of goals for the benefit of the Ummah.